1985
DOI: 10.1056/nejm198508083130602
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Coronary Angioplasty in Refractory Unstable Angina

Abstract: We performed percutaneous transluminal coronary angioplasty as an emergency procedure in 60 patients with unstable angina pectoris that was refractory to treatment with maximally tolerated doses of beta-blockers, calcium antagonists, and intravenous nitroglycerin. The initial success rate for angioplasty was 93 per cent (56 patients). There were no deaths related to the procedure, although total occlusion occurred in four patients. Despite emergency bypass grafting, all four sustained a myocardial infarction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 181 publications
(18 citation statements)
references
References 27 publications
0
17
0
1
Order By: Relevance
“…21], and the attendant cumulative costs are elevated [20], given the high preva lence of unstable angina within the hospital ized coronary artery disease population [22], PTCA, when feasible, offers the promise of quick restoration of blood flow, relief of symptoms, shortened hospitalization [20] and containment of costs [20], Its widespread use in patients with unstable angina is readily understood. The primary success rate in most reports of coronary angioplasty for unstable angina pectoris ranges from 61 in earlier stud ies [8] to 93% in more recent series when steerable systems were used [9], The success rate in unstable angina pectoris is the same or greater than that of stable angina pectoris. Meyer et al [7] described a technical success rate of 74% in unstable angina pectoris and 66% in stable angina.…”
Section: Discussionmentioning
confidence: 98%
“…21], and the attendant cumulative costs are elevated [20], given the high preva lence of unstable angina within the hospital ized coronary artery disease population [22], PTCA, when feasible, offers the promise of quick restoration of blood flow, relief of symptoms, shortened hospitalization [20] and containment of costs [20], Its widespread use in patients with unstable angina is readily understood. The primary success rate in most reports of coronary angioplasty for unstable angina pectoris ranges from 61 in earlier stud ies [8] to 93% in more recent series when steerable systems were used [9], The success rate in unstable angina pectoris is the same or greater than that of stable angina pectoris. Meyer et al [7] described a technical success rate of 74% in unstable angina pectoris and 66% in stable angina.…”
Section: Discussionmentioning
confidence: 98%
“…The VANQWISH trial (Boden et al, 1998), for example, showed raised mortality with an invasive approach early after non-Q-wave MI. However, many observational studies and the randomized TIMI IIIb trial (de Feyter et al, 1985;Anderson et al, 1995;McCullough et al, 1998) have shown shorter hospital stays, fewer readmissions, less ischemia, and fewer symptoms with an early invasive approach. In the prospective FRISC II study (FRISC II, Lancet 1999), patients were randomly assigned to an early invasive or non-invasive treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Major complications (death, urgent bypass surgery) occurred in 2 of our patients with severely depressed ventricu lar function, the procedural risk came to 5%. It has to be considered, however, that the majority of our patients suffered from unsta ble angina: PTCA in these patients is more often associated with major complications as death, myocardial infarction or urgent bypass surgery than in patients with stable angina, and it concerns 5-7% of the patients [23,[27][28][29]. In former studies reporting on acute re sults and long-term follow-up of PTCA, hospi tal mortality was 5% in patients with an ejec tion fraction of less than 35 [4] or 40% [5,18].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas mortality of PTCA gen erally amounts to 1% [19,20], mortality rises to 3-4% in these high-risk patients [4,5,18,21]. However, the success rate of PTCA in patients with seriously reduced ejection frac tion is comparable to routine angioplasty in which the success rate lies between 83 and 94% [2,19,[22][23][24][25]. Late morbidity and mor tality remain high, only about half the pa tients are unaffected by repeat cardiac events such as death, myocardial infarction, bypass surgery or repeat angioplasty [4,5,18].…”
Section: Discussionmentioning
confidence: 99%